Immediate post‐anaesthesia recovery 2013: Association of Anaesthetists of Great Britain and Ireland. (5th February 2013) - ,; Whitaker (Chair), D. K.; Booth, H.; Clyburn, P.; Harrop‐Griffiths, W.; Hosie, H.; Kilvington, B.; MacMahon, M.; Smedley, P.; Verma, R.
Summary: After general, epidural or spinal anaesthesia, all patients should be recovered in a specially designated area (henceforth 'post‐anaesthesia care unit', PACU) that complies with the standards and recommendations described in this document. The anaesthetist must formally hand over the care of a patient to an appropriately trained and registered PACU practitioner. Agreed, written criteria for discharge of patients from the PACU to the ward should be in place in all units. An effective emergency call system must be in place in every PACU and tested regularly. No fewer than two staff (of whom at least one must be a registered practitioner) should be present when there is a patient in a PACU who does not fulfil the criteria for discharge to the ward. All registered practitioners should be appropriately trained in accordance with the standards and competencies detailed in the UK National Core Competencies for Post Anaesthesia Care. All patients must be observed on a one‐to‐one basis by an anaesthetist or registered PACU practitioner until they have regained control of their airway, have stable cardiovascular and respiratory systems and are awake and able to communicate. All patients with tracheal tubes in place in a PACU should be monitored with continuous capnography. The removal of tracheal tubes is the responsibility of the anaesthetist. There should be a specially designated area for the recovery of children that is appropriately equipped and staffed. All standards and recommendations described in this document should be applied to all areas in which patients recover after anaesthesia, to include those anaesthetics given for obstetric, cardiology, imaging and dental procedures, and in psychiatric units and community hospitals. Only registered PACU practitioners who are familiar with these areas should be allocated to recover patients in them as and when required. Patients' dignity and privacy should be respected at all times but patients' safety must always be the primary concern. When critically ill patients are managed in a PACU because of bed shortages, the primary responsibility for the patient lies with the hospital's critical care team. The standard of nursing and medical care should be equal to that in the hospital's critical care units. Audit and critical incident reporting systems should be in place in all PACUs.